Introduction: genre work and the new economy. Issue 6 (2nd November 2022) - Prentice, Michael M.; Gershon, Ilana
ABSTRACT: The special issue brings together anthropologists working at the intersection of language and economy to draw attention to the dynamics of how people's experiences of social change are articulated through genre work in different institutional contexts. In recent years, many scholars working in cultural economy have turned to language as an analytic, and this has often focused on the performative dimensions of economic practice as the most significant dimension: the promulgation of financial models, statements of authority from bank leaders, and the power of numbers. While working within similar traditions, we aim to draw attention to the significant, but often overlooked, role that other kinds of genres and other kinds of genre work play for actors in and out of changing economic contexts.